THE IMPACT OF THE SPORTS INDUSTRY ON THE STATE OF THE FOOD MARKET IN A PANDEMIC - Fomin, Oleg; Nedurueva, Tatyana; Bobrovskiy, Evgeniy; Perkova, Elena (Revista Inclusiones, 2020)
The problem of the spread of coronavirus infection, which has become pandemic in many countries, has seriously affected the pace of economic development, regardless of the level of socio-economic development. Slowing economic processes led to a decrease in social mobility of the population, real incomes of citizens, which led to a drop in demand for healthy and sports nutrition products. The influence of the sports industry in promoting a healthy lifestyle, an integral part of which is a healthy diet, is obvious, but the marketing potential of cooperation between these market segments cannot be fully realized in the current conditions. Due to the reduced opportunities for promoting healthy nutrition products, the sports sector will not receive sponsorship contracts, and food producers will not receive the expected marketing effect for promoting their products on the market, which is complemented by a decrease in the purchasing power of the population in many countries of the world. Other sectors will also suffer a loss from the spread of the pandemic, the marketing promotion of which is tied to the sports industry to one degree or another.